Comparison of two impression methods for determining the neutral zone in edentulous patients - Ibragimova F.I; Arslanov K.S (Research Parks Publishers, 2021)
Although complete dentures are not ideal replacements for natural dentition, they should not be noticeable and patients should not feel uncomfortable in the mouth. The role of the action of the surrounding facial muscles, speech, and chewing is often overlooked in the manufacture of complete removable dentures. All muscle functions that include chewing, swallowing, speaking, laughing, and sucking involve the harmonious action of the lips, cheeks, tongue, and bottom of the mouth. These actions impact the design of the prosthesis and can be recorded using functional methods. Failure to recognise these functions can affect the position of the teeth, the boundaries of expansion, the location of the occlusal plane, and the contours of the polished surface, which can lead to an unstable and unsatisfactory prosthesis. The concept of the neutral zone considers the neuromuscular function that contributes to the stabilisation of the prostheses